Repeated dose inhalation developmental toxicity study in rats exposed to cellulose insulation with boric acid additive. (6th December 2018) - Pleus, Richard C.; Bruce, Gretchen; Klintworth, Heather; Sullivan, Dennis; Johnson, William; Rajendran, Narayanan; Keenan, James
Abstract: Cellulose insulation (CI), a common building material, is a mixture of cellulose fibers and borates. Borates are approximately 20% of the product weight and act as a flame retardant. Given possible exposure to workers and consumers, an inhalation toxicity study was conducted following Organization for Economic Co-operation and Development (OECD) 414 for Prenatal Development Toxicity to evaluate if CI is a developmental toxicant. Pregnant female rats were exposed by nose-only inhalation to CI aerosols containing 20% boric acid for six h/day, from gestational day (GD) 6–19, and fetuses were evaluated for developmental parameters. Respirable CI was produced by grinding to produce respirable particles (MMAD 2.7–2.9 µm, geometric standard deviations (GSD) 1.9–2.6), which were then aerosolized. Target air concentrations were 15, 90, and 270 mg CI/m 3 . Controls were exposed to air only. Slight body weight reductions (average decrease <7% vs. control) were observed in male and female GD 20 fetuses in the mid and high dose groups. No embryo/fetal developmental toxicity or alterations in any other measured variable were reported at any dose. The no observed adverse effect level (NOAEL) for developmental outcomes was 270 mg/m 3 .